Atlas of operative craniofacial surgery - Mesa, John; Buchman, Steven; Mackay, Donald R. (Professor of plastic surgery); Losee, Joseph E.; Havlik, Robert J. (Thieme, 2019)
This clinical book + videos embraces the spectrum of craniofacial surgery Written by the world's foremost experts, Atlas of Operative Craniofacial Surgery with its accompanying videos is a unique resource that offers the reader a succinct yet comprehensive guide to performing craniofacial operations. In each chapter, renowned specialists share their strategies for selecting patients, executing effective preoperative planning, comprehending detailed operative techniques, instituting postoperative care best practices, dealing with possible complications, and much more. Key Features The wide arra.